Strengthening Performance-Based Budgeting Through Standardization of Tridharma Indicators at UIN Alauddin Makassar - Muhammad Hidayat (POKJANAS PERENCANA KEMENTERIAN AGAMA RI, 2026)
This policy paper analyzes the output-based planning and budgeting system at UIN Alauddin Makassar, which continues to face serious obstacles in measuring and verifying the contribution of Tridharma (the three pillars of higher education) activities toward the university's Key Performance Indicators (KPIs). This study identifies the primary weakness in the absence of specific, measurable, and standardized performance indicators, resulting in evaluations that emphasize administrative activities rather than substantive outcomes. Further analysis reveals that weak monitoring and evaluation mechanisms, limited human resource capacity, and fragmented data systems exacerbate the ineffectiveness of performance-based budgeting. The USG (Urgency, Seriousness, Growth) method was applied to determine priority issues, indicating that the weakness of output–outcome measurement is the most critical problem. These findings demonstrate that performance measurement is not merely a technical issue but a governance problem affecting accountability, expenditure effectiveness, and evidence-based decision-making. The study recommends establishing standardized cross-unit performance indicators, integrating monitoring and evaluation systems with performance data, and strengthening analytical capacity as strategic measures to ensure that planning and budgeting systems genuinely support measurable and sustainable institutional goals.